GRAMMATICAL ERRORS ANALYSIS OF THE THIRD SEMESTER STUDENTS’ RECOUNT ESSAYS - Linda Linda; Hanandyo Dardjito (Universitas Sarjanawiyata Tamansiswa, 2020)
Considering the importance of students’ errors in English learning process, this research was conducted to identify grammatical errors made by the third semester students of Universitas Sarjanawiyata Tamansiswa. Two research questions are put forward in this error analysis research. They are (1) What are the grammatical errors types made by the students when they write a recount essay? (2) What is the most grammatical error made by the students? This research applied a descriptive qualitative method with the students’ writing as the key data. The data were collected using the writing assignments of the writing lecturer. James’ theory of grammatical error categories and Corder’s theory of error analysis procedure became the main baseline theories in the data analysis. The data used in this research were collected from 16 scripts written by the third semester students. The findings show that there were 245 errors figured out in students’ recount essays. This research further revealed that 138 (56.3%) of the whole error were related to inappropriate usage of tenses. It was the most dominant error appearing in students’ writings. This category was followed by the errors of prepositions usage with a frequency of 31 (12.6%), poor usage of articles with a frequency of 29 (11.8%), errors of singular/plural with a frequency of 21 (8.6%), improper use of irregular verbs with a frequency of 11 (4.5%), poor usage of adjectives with a frequency of 7 (2.9%), inability to apply the rules of concord with a frequency of 6 (2.5%), and possessive case with a frequency of 2 (0.8%). These errors indicated students lacked of grammatical knowledge and had not been able to write an acceptable writing especially a recount text.